انفصال العمارة عن الطبيعة خلال القرن العشرين مدينة اللاذقية مثالا" - خضرة فؤاد; غره رنا (Latakia University Journal -Engineering Sciences Series, 2016)
للمجتمع الإنساني وتطوره ارتباط مميز بالعمارة التي تشكل ظاهرة لها غايات مختلفة أهمها الاجتماعية وتصنع ما يُطلق عليه مصطلح "البيئة المعمَرة " الناتجة عفوياً من دورها في إرضاء احتياجات الإنسان وخاصة الاجتماعية منها. تراجع هذا الدور مع بدايات القرن الماضي وكان نتيجته الانفصال بين العمارة وبيئتها في مدينة اللاذقية على شكل تلوث ذوقي وحسي لمبانيها مبتعداً بها عن خصوصيتها كظاهرة حية مرتبطة بعصرها ومجتمعها. وبمنهجية تدرجت من التعرف على العمارة الإنسانية وما تفعله لتوثيق الإرتباط بين الإنسان والطبيعة والعلاقة بين العمارة ومحيطها والوضع الراهن والأسباب التي أدت إلى هذا الانفصال بينهما من خلال تحليل مظاهره للوصول إلى حلول معمارية تعيد علاقة الإرتباط بين عمارة المدينة ووسطها الطبيعي. يختتم البحث بتوصيات ونتائج يمكن أن تُكوّن نواة لإعادة الارتباط بين العمارة وبيئتها من خلال عودة الدور المنوط بها. بحث مسجل بقرار مجلس الجامعة رقم /52/ تاريخ 17/9/2013 وأُجري في كلية الهندسة المعمارية بجامعة تشرين بين 17/9/2013 و 17/6/2014. The Human society and its development has a great link with architecture that forms a phenomenon with different objectives; the most important of these are the social ones that make what is called "the built environment" that stemmed spontaneously from its role in satisfying human needs, especially the social ones. This role was reduced at the beginnings of the pervious century and the result was a separation between architecture and its community in Lattakia city as a kind of aesthetic and sensual pollution for its buildings keeping it away from its peculiarity as a living phenomenon that is linked with its era and society. A system that moved from identifying the human architecture to strengthen the relation between humans and nature, and the relation between nature and its surrounding, the current situation and reasons that led to this separation between the urban architecture and its natural surroundings. The research concludes with recommendations and conclusions that might be a core to re-establish the relation between the architecture and surroundings through its regaining its role.